2008
DOI: 10.1111/j.1468-2311.2008.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

A not so Well‐Lit Path: Employers' Perspectives on Employing Ex‐offenders

Abstract: Findings from a recent survey among employers in the north-west of England suggest that personal support is the most favoured type of support both for employers and for ex-offenders when considering employing (or employing more) ex-offenders. The findings also reveal that employers need more information on the relevance and the provisions of the Rehabilitation of Offenders Act 1974, as well as guidance on risk assessment and management procedures, in order to enable them to make informed decisions about, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 2 publications
3
31
1
Order By: Relevance
“…Employers who are younger, have tertiary qualifications, work in larger companies and/or report a previous positive experience hiring an ex-offender are more likely to report favourable attitudes towards employing ex-offenders (Fahey, et al, 1996;Graffam, Shinkfield, Lavelle & Hardcastle, 2004;Haslewood-Pócsik, Brown & Spencer, 2008;Lukies, et al, 2011;). …”
Section: Introductionmentioning
confidence: 99%
“…Employers who are younger, have tertiary qualifications, work in larger companies and/or report a previous positive experience hiring an ex-offender are more likely to report favourable attitudes towards employing ex-offenders (Fahey, et al, 1996;Graffam, Shinkfield, Lavelle & Hardcastle, 2004;Haslewood-Pócsik, Brown & Spencer, 2008;Lukies, et al, 2011;). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, existing literature and government initiatives emphasized the importance of using work as a means to improve health outcomes (17)(18)(19), and reduce re-offending rates among offenders (22). However, barriers to employment among patients with offending histories are numerous, including stigma, homelessness, substance misuse, negative attitudes among employers, and lack of relevant skills and qualifications (7,23,24). Furthermore, evidence from the UK suggests that while it is possible to support offenders with mental disorders into mainstream employment, only a minority of these individuals are offered help (7).…”
Section: Employment Supportmentioning
confidence: 99%
“…In the UK, lack of employment support costs (e.g., criminal record checks, uniforms, travel to interviews) have been identified as additional barrier (30). Furthermore, employers may reluctant to employ people with offending histories especially sex offenders (24). While the IPS model originated in the USA, several studies demonstrated that IPS can transport successfully to other countries including the UK (58,59).…”
Section: Feasibility Issuesmentioning
confidence: 99%
“…Haslewood -Pócsik, Brown, and Spencer (2008) examined several topics related to employing formerly convicted individuals in northwest England and found support for many of the abovementioned factors. 16 Noteworthy is that, next to job skills, several "soft skills" such as honesty and reliability were rated as highly relevant characteristics.…”
Section: Employer Willingness To Hirementioning
confidence: 99%